Arabidopsis thaliana Roots Exposed to Extracellular Self-DNA: Evidence of Epigenetic Effects - Alessia Ronchi; Guido Incerti; Emanuele De Paoli; Speranza Claudia Panico; Giovanni Luca Sciabbarrasi; Pasquale Termolino; Fabrizio Cartenì; Mariachiara Langella; Maria Luisa Chiusano; Stefano Mazzoleni (Epigenomes, 2025)
Background: Previous evidence demonstrated DNA methylation changes in response to stress in plants, showing rapid changes within a limited time frame. Exposure to self-DNA inhibits seedling root elongation, and it was shown that it causes changes in CG DNA methylation in Lactuca sativa. We assessed cytosine methylation changes and associated gene expression patterns in roots of Arabidopsis thaliana Col-0 seedlings exposed to self-DNA for 6 and 24 h. Methods: We used whole genome bisulfite sequencing (WGBS) and RNA-seq analyses to assess genomic cytosine methylation and corresponding gene expression, respectively, on DNA and RNA extracted with commercial kits from roots exposed to self-DNA by an original setup. Fifteen hundred roots replicates, including the control in distilled water, were collected after exposure. Sequencing was performed on a NovaSeq 6000 platform and Ultralow Methyl-Seq System for RNA and DNA WGBS, respectively. Results: Gene expression in roots exposed to self-DNA differed from that of untreated controls, with a total of 305 genes differentially expressed and 87 ontologies enriched in at least one treatment vs. control comparison, and particularly after 24 h of exposure. DNA methylation, particularly in CHG and CHH contexts, was also different, with hyper- and hypomethylation prevailing in treatments vs. controls at 6 h and 24 h, respectively. Differentially expressed genes (DEGs) analysis, Gene Ontology (GO) enrichment analysis, and differentially methylated regions (DMRs) analysis, provided an integrated understanding of the changes associated with self-DNA exposure. Our results suggest differential gene expression associated with DNA methylation in response to self-DNA exposure in A. thaliana roots, enhanced after prolonged exposure. Conclusions: Main functional indications of association between DNA methylation and gene expression involved hypomethylation and downregulation of genes related to nucleotide/nucleoside metabolism (ATP synthase subunit) and cell wall structure (XyG synthase), consistent with previous observations from metabolomics and physiological studies. Further confirmation of these findings will contribute to improving our understanding of the plant molecular response to self-DNA and its implications in stress responses.